1986
DOI: 10.1002/jcb.240310106
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between protease activity and a sialoglycopeptide inhibitor isolated from bovine brain

Abstract: We have recently described the isolation and purification to homogeneity of a new sialoglycopeptide from bovine brain cell surfaces that reversibly inhibits protein synthesis and DNA synthesis of normal but not transformed cells. Active inhibitory preparations, however, were shown to contain a protease activity that was not lost upon purification. Several experiments were performed to establish the relationship between the proteolytic activity of the sialoglycopeptide and the biological inhibitory activity. Bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

1986
1986
1995
1995

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…It has been shown that the sialoglycopeptide contains a unique protease activity that could not be dissociated from the inhibitory activity (Sharifi et al, 1986b). However, our data are inconsistent with the protease activity being responsible for mediating the biological effect of the sialoglycopeptide.…”
Section: Discussionmentioning
confidence: 45%
See 1 more Smart Citation
“…It has been shown that the sialoglycopeptide contains a unique protease activity that could not be dissociated from the inhibitory activity (Sharifi et al, 1986b). However, our data are inconsistent with the protease activity being responsible for mediating the biological effect of the sialoglycopeptide.…”
Section: Discussionmentioning
confidence: 45%
“…We have been interested in understanding the mechanisms of density-dependent regulation of cell growth for several years (Kinders et al, 1980;Kinders and Johnson, 1982;Johnson et al, 1985). We recently purified a 18,000 dalton sialoglycopeptide (PI 3.0) that inhibits protein synthesis and DNA synthesis of non-transformed but not transformed cells while not afl'ecting uptake of radiolabeled precursors (Sharifi et al, 1986a;Sharifi et al, 1986b).…”
mentioning
confidence: 99%
“…The purified 18 kD sialoglycopeptide has a PI of 3.0, is composed of a single polypeptide without subunit structure, and has a unique protease activity [12]. Although the protease cannot be physically resolved from the inhibitor, the enzymatic activity is not responsible for the biological inhibitory activity [13].…”
mentioning
confidence: 99%
“…We have recently isolated and purified, from bovine cerebral cortex cell surfaces, a sialoglycopeptide that reversibly inhibits protein and DNA synthesis of a variety of normal cells without altering the uptake of radiolabeled precursors [ 10,111. The purified 18 kD sialoglycopeptide has a PI of 3.0, is composed of a single polypeptide without subunit structure, and has a unique protease activity [12]. Although the protease cannot be physically resolved from the inhibitor, the enzymatic activity is not responsible for the biological inhibitory activity [13].…”
mentioning
confidence: 99%